2020
DOI: 10.1108/jocm-05-2019-0136
|View full text |Cite
|
Sign up to set email alerts
|

Corporate acceleration process: a systems psychodynamics perspective

Abstract: PurposeThe purpose of this paper is to explore the emotional dynamics of the corporate acceleration process, using the systems psychodynamics perspective.Design/methodology/approachThe study applies inductive multiple case study of embedded 10 cases of corporate acceleration, covering both incumbent and startup perspectives, occurring in the context of a corporate accelerator.FindingsWe find that (1) the process of corporate acceleration involves three phases, each of them is dominated by a different emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…(n.r. = not ranked) The track record seemed to be a key criterion in the start-up selection process: a track record including prior experience in founding start-ups (Wójcik et al, 2020), investments by other investors (Ben Mahmoud-Jouini et al, 2018;Chemmanur et al, 2014;Ozmel et al, 2017;Park and Steensma, 2013;Park and Bae, 2018), or a previous affiliation with the respective corporation (Henderson, 2009;Wójcik et al, 2020) increased a start-up's chances of being selected for external corporate venturing activities. Whereas one study found that corporates were not interested in the entrepreneur(s) business qualification (Henderson, 2009), other studies supported the view that a higher level of education both in the field of science and engineering but also from other disciplines increased the chances of being selected (Andersson and Xiao, 2016).…”
Section: Expert Interviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…(n.r. = not ranked) The track record seemed to be a key criterion in the start-up selection process: a track record including prior experience in founding start-ups (Wójcik et al, 2020), investments by other investors (Ben Mahmoud-Jouini et al, 2018;Chemmanur et al, 2014;Ozmel et al, 2017;Park and Steensma, 2013;Park and Bae, 2018), or a previous affiliation with the respective corporation (Henderson, 2009;Wójcik et al, 2020) increased a start-up's chances of being selected for external corporate venturing activities. Whereas one study found that corporates were not interested in the entrepreneur(s) business qualification (Henderson, 2009), other studies supported the view that a higher level of education both in the field of science and engineering but also from other disciplines increased the chances of being selected (Andersson and Xiao, 2016).…”
Section: Expert Interviewsmentioning
confidence: 99%
“…Incumbents seemed to use their external corporate venturing activities as a source of innovation (Andersson and Xiao, 2016;Ben Mahmoud-Jouini et al, 2018;Benson and Ziedonis, 2009;Chemmanur et al, 2014;Enkel and Sagmeister, 2020;Ma, 2020;Park and Steensma, 2013;Wójcik et al, 2020). In the identified studies, incumbents selected start-ups that developed new products, innovative services, or unique solutions with a specific value for the incumbent (Ben Mahmoud-Jouini et al, 2018;Enkel and Sagmeister, 2020;Hamilton, 2001;Henderson, 2009;Kanbach and Stubner, 2016;Lantz et al, 2011;Prashantham and Kumar, 2019;Wójcik et al, 2020).…”
Section: Product and Technology Criteria Identified In The Systematic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The material was a study of 10 cases where the points of view of both a start-up and a corporation were taken into account. This study is expected to contribute to a better understanding of the corporate-start-up relationship and recommend how to better manage corporate accelerators, enhancing their effectiveness, from a perspective that has never been considered before (Wójcik et al, 2020).…”
Section: Corporate Acceleratorsmentioning
confidence: 99%
“…The research was based on the analysis of 10 case studies in terms of emotional dynamics from a systems psychodynamic perspective. The study included the points of view of both a corporation and a startup [Wójcik et al, 2020].…”
Section: Systematic Literature Reviewmentioning
confidence: 99%